Survey of the Relationship between Health Literacy Level and Health Sstatus among Elderly People Referring to Retirement Centers in Rasht city - Nasrin Mokhtari; Afsaneh Nezafati; Farzaneh Sheikholeslami; Ehsan Kazemnejad Leili (Golestan University of Medical Sciences, 2019)
Background and objectives: Lower levels of health literacy have been associated with adverse health outcomes, especially for elderly. Methods: This cross-sectional study was conducted on 290 retired elder from the Retirement Centers in Rasht city by Convenient sampling during the year 2017. Data collection tools included, Test of Functional Health Literacy in Adults(TOFHLA) and general health standard questionnaire (GHQ-28). The data were analyzed using descriptive and inferential statistics in SPSS. Results: More than half of the participants (54.8%) had adequate health literacy. The highest mean of the health literacy was in the domain of reading comprehension (36.30±7.90) and then in the domain of numeracy (36.11±11.60). There was a significant relationship between the level of health literacy and the level of education, the level of education of the spouse and the history of cancer(P<0.05), the mean of the general health of the subjects was 20.67±8.27. by adjusting the effects of demographic variables, there was a significant relationship between the health literacy and the general health (P=0.04), such that by improving each level in the health literacy status, the chance of a favorable general health status, increases by 1.4 times (Odds Ratio=1.4).The findings, show a 0.95 confidence interval for variables related to general health. Conclusion: This study approved that the level of education was the most important determinant of health literacy and general health, identifying elderly with poor health literacy and providing them with appropriate education can play a major role in promoting community health.